2008
DOI: 10.1021/jf072025o
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Spectroscopy: A Rapid Tool for Analyzing Dairy Products

Abstract: This paper gives a critical evaluation of the use of fluorescence spectroscopy for measuring chemical and physical changes in dairy products caused by processing and storage. Fluorescence spectroscopy is able to determine various properties of foods without use of chemicals and time-consuming sample preparation. This is shown by examples where the measurement of a given chemical parameter has been appropriately described and validated, as well as situations showing potential applications, but where further res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 59 publications
3
108
1
Order By: Relevance
“…So, loadings are an overall photography of changes in the samples mainly due to their botanical origins. Figure 15 presents an overview of the main fluorophores potentially present in dairy and food products [63,93] …”
Section: Pca: the Basic Building Block Of Chemometrics 31mentioning
confidence: 99%
“…So, loadings are an overall photography of changes in the samples mainly due to their botanical origins. Figure 15 presents an overview of the main fluorophores potentially present in dairy and food products [63,93] …”
Section: Pca: the Basic Building Block Of Chemometrics 31mentioning
confidence: 99%
“…[1][2][3][4] Several fluorescent techniques have been developed to detect various target analytes. Fluorescent sensors based on fluorescence dyes, such as fluorescein isothiocyanate and FAM labels, have been a general routine for biological applications, especially imaging and assays.…”
Section: Introductionmentioning
confidence: 99%
“…A versatile signal-on fluorescence sensing strategy based on SGI and GO y=7.4001C TP(nM) +13.2151 (3) in which R=0.9888 and the slope of the calibration curve was 7.4001. Compared with the best-fit curve in Figure 6B (with the slope of 7.4922), the proximity of the slope of the calibration curve in Figure 8B indicated that the proposed assay could accurately work to detect MDR1 gene in the serum.…”
mentioning
confidence: 99%
“…In particular, aflatoxin analysis of aflatoxins in spices is complex because of the interference of highly colored materials that are coextracted with aflatoxins. For the above method, an elaborate cleanup process, using the above columns, is necessary before stance in a mixture (Andersen and Mortensen, 2008;Booksh et al, 1996;Shimoyama and Noda, 1992;Tsuta et al, 2007). The FF method is highly sensitive compared with typical fluorescence measurements because the FF method uses all spectral data, consisting of excitation × emission × fluorescence intensities.…”
Section: Introductionmentioning
confidence: 99%
“…FF measurement has several merits in practical and commercial applications, since it requires no complex preprocessing and is nondestructive (Andersen and Mortensen 2008;Yin et al, 2009;Shibata et al, 2011;Fujita et al, 2012;Kokawa et al, 2011). Fujita et al (2012) successfully predicted the concentrations of two Fusarium mycotoxins in fungus-contaminated wheat flour using FF, with high accuracy and nondestructively.…”
Section: Introductionmentioning
confidence: 99%